2018
DOI: 10.1111/sifp.12060
|View full text |Cite
|
Sign up to set email alerts
|

Birth Planning and Women's and Men's Health in Malawi

Abstract: Despite the frequency with which it occurs, we know little about unintended fertility in sub-Saharan Africa and even less about its implications for the health of the women and men who experience it. We use longitudinal data from southern Malawi to explore how young adults report on the planning of their births and to identify changes in their self-rated health and subjective well-being associated with having more- or less-planned births. Our data feature a comprehensive scale of pregnancy planning, the London… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…42,43 The LMUP has now been adapted several times for administration to women's partners because of the need for a comparable measure of pregnancy intention when researching couples. [44][45][46][47][48] The first adaptation was in the UK when a screening tool was needed to find young men with planned pregnancies for an interview study. 44 Subsequent adaptations for men were in Sweden and Malawi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…42,43 The LMUP has now been adapted several times for administration to women's partners because of the need for a comparable measure of pregnancy intention when researching couples. [44][45][46][47][48] The first adaptation was in the UK when a screening tool was needed to find young men with planned pregnancies for an interview study. 44 Subsequent adaptations for men were in Sweden and Malawi.…”
Section: Discussionmentioning
confidence: 99%
“…44 Subsequent adaptations for men were in Sweden and Malawi. 45,47 In keeping with international guidelines, [49][50][51] an analysis of the psychometric properties of the adapted measure is required to know whether an adaptation for partners is valid. So far, the only evaluation of psychometric properties that has been carried out has been with the Malawian Chichewa-language version for men, which showed excellent psychometric properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The concentration of unintended births on the continent makes it critically important to understand their impact on women's health. Most research on the risks of unintended births for women's health focuses on maternal health in pregnancy and the postpartum period, yet the implications of having an unanticipated child could extend well beyond the postpartum period to scar women's general physical and mental health even years later (Brittain et al 2019;Gipson, Koenig, and Hindin 2008;Herd et al 2016;Yeatman and Smith-Greenaway 2018). However, serious measurement and design challenges in this area leave open the possibility that identified relationships are driven by retrospective reporting biases rather than true impacts (Gipson, Koenig, and Hindin 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Since these data were collected there has been one other assessment of the psychometric properties of the Chichewa LMUP in Malawi by Yeatman and Greenaway [ 25 ]. In their study of 645 women, the Chichewa LMUP also demonstrated excellent psychometric properties: Chronbach’s alpha = 0.86; all item-rest correlations > 0.2, including the contraception and preconception questions; principal components analysis demonstrating one component/unidimensional measurement; and a full range of scores with a bimodal distribution.…”
Section: Main Textmentioning
confidence: 99%